The Torah on life and death. Jewish bioethics in dialogue - Szymczyk, Marta (Diametros, 2007)
Review of a book: Tomasz P. Terlikowski, Tora między życiem a śmiercią. Bioetyki żydowskie w dialogu, Wydawnictwo RHETOS, Warszawa 2007.